DEVELOPING VOCATIONAL SCHOOL STUDENTS’ READING SKILL USING QUESTION-ANSWER RELATIONSHIPS THROUGH GOOGLE CLASSROOM - Andhi Dwi Nugroho; Luthfiana Nur Na’imah; Teguh Bangkit Pamungkas; Oktaviani Windra Puspita; Rizal Rizal (JELLT (Journal of English Language and Language Teaching), 2021)
The study aimed to investigate how Question-Answer Relationships (QAR) through Google Classroom (GC) develop the vocational school students’ reading skill and expose the benefits of its implementation. QAR through GC was expected to fulfil the students’ need, especially improving their reading skill. The data were collected by test, observation, interview, and questionnaire. The subjects of the study are the tenth graders of one state and three private vocational schools in Yogyakarta. The study employed classroom action research (CAR) consisted of two cycles included four steps: planning, acting, observing and reflecting. In the first cycle, the mean score of pre-test was 58.58. However, in the second cycle, the mean score of post-test was 69.85. The gain score between tests was 11.27, and the t score was - 3.72 (p-value < 0.05). This proved that Question-Answer Relationship through Google Classroom was effective to teach reading. In addition, the study revealed three advantages of implementing QAR through GC such as conducting interesting and safe medium online learning, helping students to discuss the material, and engaging the students’ motivation in learning reading.